2016
DOI: 10.1371/journal.pone.0158979
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica Trophozoites and Lipopeptidophosphoglycan Trigger Human Neutrophil Extracellular Traps

Abstract: Neutrophil defense mechanisms include phagocytosis, degranulation and the formation of extracellular traps (NET). These networks of DNA are triggered by several immune and microbial factors, representing a defense strategy to prevent microbial spread by trapping/killing pathogens. This may be important against Entamoeba histolytica, since its large size hinders its phagocytosis. The aim of this study was to determine whether E. histolytica and their lipopeptidophosphoglycan (EhLPPG) induce the formation of NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 55 publications
2
50
0
1
Order By: Relevance
“…Then 100 μl of 120 nM PMA in PBS, or 100 μl of an E. histolytica suspension or an E. dispar suspension (1.25 × 10 5 cell/ml) was added to each well. The amoeba to neutrophil ratio was 1:20, as determined previously . Plates were incubated in 5% CO 2 at 37°C for 4 h. Next, 600 μl of 2% paraformaldehyde with 150 nM DAPI in PBS were gently added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then 100 μl of 120 nM PMA in PBS, or 100 μl of an E. histolytica suspension or an E. dispar suspension (1.25 × 10 5 cell/ml) was added to each well. The amoeba to neutrophil ratio was 1:20, as determined previously . Plates were incubated in 5% CO 2 at 37°C for 4 h. Next, 600 μl of 2% paraformaldehyde with 150 nM DAPI in PBS were gently added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…NET function as a physical barrier where pathogens get trapped and can be eliminated extracellularly and independently of phagocytosis . Recently, we have found that E. histolytica trophozoites are capable of inducing NET formation . This response is triggered by an unknown receptor, nevertheless we were able to determine that E. histolytica induce a signaling pathway that involves Raf/MEK/ERK, and it is independent of protein kinase C and reactive oxygen species (ROS) …”
Section: Introductionmentioning
confidence: 95%
“…This protozoan parasite causes amebiasis, amoebic colitis, and hepatic abscess. Since this parasite is too large to be phagocytosed, Avila et al [43] analyzed the possibility that this parasite induces the formation of NETs. These authors demonstrated that the amoeba lipopeptidophosphoglycan induces NETs in a dose-dependent manner.…”
Section: Neutrophil Extracellular Traps In Parasitic Infectionsmentioning
confidence: 99%
“…Resistance to NETs exposure was also studied upon addition of a proteases inhibitor, resulting in that proteases are not responsible for trophozoite resistance to NETs. However, the use of ethylene glycolbis(β-aminoethyl ether)-N,N,N',N'-tetraacetic acid (EGTA), a divalent anion chelant, had a deleterious efect in the growth of amoebas that were in contact with NETs, suggesting that trophozoites may have DNAse activity, responsible for its resistance to NETs [43].…”
Section: Neutrophil Extracellular Traps In Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation